Democracy And The Sultanate System In Malaysia: The Role Of The Monarchy - Das, Cyrus (Journal of Malaysian and Comparative Law, 2019)
In this paper I propse to discuss briefly the structural features of the system of parliamentary democracy in Malaysia and examine how it relates to the traditional system of the monarchy. The uniqueness of the Malaysian Constitution lies in the blending of the features of the Westminster export model and the indigenous characteristics of feudal Malay society called the "traditional elements" of the Constitution. The origins of the Constitution may therefore be said to antedate the attainment of Independent by the country in 1957. In this regard the Constitution may not be treated as evolutionary in character and not merely an Anglo-Malayan product as suggested in some judicial pronouncements.